The Role of Place in Ecological Conversion - McDonnell, Kevin L. (The way, 2022)
The article discusses the role of place in ecological conversion. It analyzes the place-journey tension that is integral to spirituality and desire for freedom of movement. It describes the stages of intimacy required for ecological conversion and outlines processes used to foster environmental and ecological conversion. It also identifies personal values, attitudes and behaviours in relation to nature that are indicative of ecospirituality and environmental conversion.